Myt1l haploinsufficiency leads to obesity and multifaceted behavioral alterations in mice - Markus Wöhr; Wendy M. Fong; Justyna A. Janas; Moritz Mall; Christian Thome; Madhuri Vangipuram; Lingjun Meng; Thomas C. Südhof; Marius Wernig (Molecular Autism)
Abstract Background The zinc finger domain containing transcription factor Myt1l is tightly associated with neuronal identity and is the only transcription factor known that is both neuron-specific and expressed in all neuronal subtypes. We identified Myt1l as a powerful reprogramming factor that, in combination with the proneural bHLH factor Ascl1, could induce neuronal fate in fibroblasts. Molecularly, we found it to repress many non-neuronal gene programs, explaining its supportive role to induce and safeguard neuronal identity in combination with proneural bHLH transcriptional activators. Moreover, human genetics studies found MYT1L mutations to cause intellectual disability and autism spectrum disorder often coupled with obesity. Methods Here, we generated and characterized Myt1l-deficient mice. A comprehensive, longitudinal behavioral phenotyping approach was applied. Results Myt1l was necessary for survival beyond 24 h but not for overall histological brain organization. Myt1l heterozygous mice became increasingly overweight and exhibited multifaceted behavioral alterations. In mouse pups, Myt1l haploinsufficiency caused mild alterations in early socio-affective communication through ultrasonic vocalizations. In adulthood, Myt1l heterozygous mice displayed hyperactivity due to impaired habituation learning. Motor performance was reduced in Myt1l heterozygous mice despite intact motor learning, possibly due to muscular hypotonia. While anxiety-related behavior was reduced, acoustic startle reactivity was enhanced, in line with higher sensitivity to loud sound. Finally, Myt1l haploinsufficiency had a negative impact on contextual fear memory retrieval, while cued fear memory retrieval appeared to be intact. Limitations In future studies, additional phenotypes might be identified and a detailed characterization of direct reciprocal social interaction behavior might help to reveal effects of Myt1l haploinsufficiency on social behavior in juvenile and adult mice. Conclusions Behavioral alterations in Myt1l haploinsufficient mice recapitulate several clinical phenotypes observed in humans carrying heterozygous MYT1L mutations and thus serve as an informative model of the human MYT1L syndrome.